Nonparametric identification of accelerated failure time competing risks models - Sokbae Lee; Arthur Lewbel (Centre for Microdata Methods and Practice (cemmap), 2010)
We provide new conditions for identification of accelerated failure time competing risks models. These include Roy models and some auction models. In our set up, unknown regression functions and the joint survivor function of latent disturbance terms are all nonparametric. We show that this model is identified given covariates that are independent of latent errors, provided that a certain rank condition is satisfied. We present a simple example in which our rank condition for identification is verified. Our identification strategy does not depend on identification at infinity or near zero, and it does not require exclusion assumptions. Given our identification, we show estimation can be accomplished using sieves.
Keywords: 330; accelerated failure time models; competing risks; identifiability; Fehlzeit; Risiko; Nichtparametrisches Verfahren; Modellierung